2023
DOI: 10.1001/jamanetworkopen.2023.12147
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Care Barriers, Use, and Health Outcomes in Younger Adults With Type 1 and Type 2 Diabetes

Abstract: ImportanceTreatment challenges exist for younger adults with type 1 (T1D) and type 2 diabetes (T2D). Health care coverage, access to, and use of diabetes care are not well delineated in these high-risk populations.ObjectiveTo compare patterns of health care coverage, access to, and use of diabetes care and determine their associations with glycemia among younger adults with T1D and with T2D.Design, Setting, and ParticipantsThis cohort study analyzed data from a survey that was jointly developed by 2 large, nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Young adults with type 2 diabetes experience many of the developmental challenges faced by peers with type 1 diabetes, such as changes in support networks, responsibilities, and health care systems. 37 The few cross-sectional studies assessing the association of psychosocial factors with HbA 1c in young adults with type 1 diabetes reported that depression, 38 diabetes distress, 39 anxiety disorders, 40 social support, 41 and health care coverage insecurity 42 were associated with HbA 1c . However, because the management of type 1 diabetes frequently involves technologies (eg, insulin pumps and continuous glucose monitoring) that pose unique challenges, it is important to study the 2 groups separately and in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Young adults with type 2 diabetes experience many of the developmental challenges faced by peers with type 1 diabetes, such as changes in support networks, responsibilities, and health care systems. 37 The few cross-sectional studies assessing the association of psychosocial factors with HbA 1c in young adults with type 1 diabetes reported that depression, 38 diabetes distress, 39 anxiety disorders, 40 social support, 41 and health care coverage insecurity 42 were associated with HbA 1c . However, because the management of type 1 diabetes frequently involves technologies (eg, insulin pumps and continuous glucose monitoring) that pose unique challenges, it is important to study the 2 groups separately and in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar efforts should be made to capture diabetes type in population-based survey data, given prior evidence showing that patients with type 1 versus type 2 diabetes may have different SDOH profiles, with implications for downstream mortality risk. 38 Uncovering these incompletely understood differences and the extent to which they affect the diabetes–mortality association could inform risk stratification and care pathways for adults with type 1 or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The ACA and Medicaid expansion are seen as important tools for increasing access to care and use of preventive services, and affected health-care utilization for young adults with DM. Using a large study cohort of 1371 participants from 2 large national cohorts in the SEARCH and the TODAY study (mean age 25 years [range, 18-36 years]), young adults with T2D were found to have less health-care coverage, and less access to and use of DM care compared to young adults with T1D [ 58 ]. Furthermore, less access was associated with higher HbA 1c .…”
Section: Factors Influencing Health-care Utilization In Young Adultsmentioning
confidence: 99%